Challenges of Adopting Blockchain Technology in Improving SME Performance - Nur Diana; Maslichah Maslichah; Dewi Diah F; Agus Hermawan; Pujihandayati Pujihandayati (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The rise of technological innovation in the era of the Industrial Revolution 4.0 has caused a breakthrough in various lines of life, including the economy. One of the technological innovations is the blockchain that can also be exploited by SMEs. This study is a literature review study that aims to provide an overview of the benefits of blockchain adoption on SMEs, the factors driving its use, and the challenges of blockchain. The use of blockchain in SMEs can facilitate in terms of more transparent, effective, efficient supply chain management. Easier in terms of delivering goods more on time so that it can ultimately deliver customer satisfaction and make a competitive advantage. The use of blockchain can also make SMEs more internationalized by collaborating with foreign e-commerce. Factors that can drive SMEs to adopt the blockchain are perceived ease of use, perceved of usefullness, performance expectancy, effort expectance, social influence, facilitating condition, trust, and relative advantage. But the obstacles to adoption are risk perceptions, security perception, low awareness, and minimal digital infrastructure. This paper is expected to give SMEs an insight into the importance of blockchain adoption to increase their performance.